Историко-краеведческая периодика Сибири и Дальнего Востока в 90-е гг. ХХ - начале XXI в.: издательские и творческие аспекты1 (Библиосфера)
The author considers the questions of developing regional-historical periodicals in Siberia and the Far East. Sharp increase of their quantity during perestrojka and especially in post-Soviet period as a reaction on breaking bureaucratic bans and establishing the freedom of historical knowledge are shown. Situational analysis with the publishing of this literature in each regional centre is given. Information is given on publishers and organizations, issuing regional-historical periodicals in the East of Russia.